2018
DOI: 10.3389/fimmu.2018.02352
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis-Associated Autoimmunity Due to Aggregatibacter actinomycetemcomitans and Its Resolution With Antibiotic Therapy

Abstract: Background: Aggregatibacter actinomycetemcomitans (Aa) is a Gram-negative coccobacillus recognized as a pathogen in periodontitis and infective endocarditis. By producing a toxin (leukotoxin A, LtxA) that triggers global hypercitrullination in neutrophils, Aa has been recently linked to rheumatoid arthritis (RA) pathogenesis. Although mechanistic and clinical association studies implicate Aa infection in the initiation of autoimmunity in RA, direct evidence in humans is lacking.Case:We describe a 59-year-old m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 26 publications
0
39
0
3
Order By: Relevance
“…The infection by periodontitis-causing bacteria, such as Porphyromomas gingivalis (P. gingivalis) and Aggregatibacter actinomycetemcomitans (Aa), as well as intestinal microbiota, likely contributes to ACPA-associated RA pathogenesis [91][92][93][94][95]. The bacterial pore-forming virulence and calcium ionophores, such as ionomycin and calcimycin from Streptomyces species and leukotoxin A from Aa, are important in triggering calcium influx and generating non-tolerized neo-citrullinated epitopes [27][28][29]. Citrullination in P. gingivalis-related periodontitis works through different mechanisms.…”
Section: Environmental Factors and Acpa Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infection by periodontitis-causing bacteria, such as Porphyromomas gingivalis (P. gingivalis) and Aggregatibacter actinomycetemcomitans (Aa), as well as intestinal microbiota, likely contributes to ACPA-associated RA pathogenesis [91][92][93][94][95]. The bacterial pore-forming virulence and calcium ionophores, such as ionomycin and calcimycin from Streptomyces species and leukotoxin A from Aa, are important in triggering calcium influx and generating non-tolerized neo-citrullinated epitopes [27][28][29]. Citrullination in P. gingivalis-related periodontitis works through different mechanisms.…”
Section: Environmental Factors and Acpa Productionmentioning
confidence: 99%
“…The revolutionary model for RA development stated that a 'second hit' may be required beyond the presence of ACPAs in disease induction [25]. As cigarette smoking and mucosal pathogens are both capable of activating peptidyl arginine deiminase (PAD) and generating citrullinated neoantigens [26][27][28][29], the accumulation of citrullinated antigens and strong immune triggers provided by the virulent agents within the smoke or microbe can possibly attract and activate dendritic cells and B cells for sequential antibody production [25]. With the help of human leukocyte antigen (HLA) molecules, interactions among antigen-specific B cells, T cells and antigen presenting cells (APCs) in the secondary lymphoid organs further promote the maturation of ACPAs [25].…”
Section: Introduction: Overview Of Acpas In Patients With Rheumatoid mentioning
confidence: 99%
“…ACPAs from ACPA-positive RA patients have been shown to cross-react with these bacterium-derived citrullinated molecules [131], and it has been suggested that the presence of these bacteria in an immunogenic context in the gums might be responsible for the triggering of some of the ACPAs in RA patients [130]. However, the relationships between periodontitis and RA are complex, and available data suggest that periodontitis and the presence of P. gingivalis per se may not be responsible for triggering of ACPA production in RA, but that immune activation rather occurs in a context of inflammation and genetics, where P. gingivalis and other bacteria including Aggregatibacter actinomycetemcomitans may be involved [133].…”
Section: Effects Of Microbial Agents Including the Microbiomementioning
confidence: 99%
“…Aforementioned process probably plays a role in many autoimmune diseases but have been recognized for only a few. The clinical importance is high because antimicrobial treatment may resolve the initial infection, once the autoimmune disease has developed it may be too late (Mukherjee et al, 2018). Alternatively, it explains why steroid anti-inflammatory treatment worsens (Clark et al, 1985) rather than improves the symptoms.…”
Section: Loss Of Tolerance and Development Of Autoimmune Diseasesmentioning
confidence: 99%